Research on real-time on-line temperature monitoring technology based on NTC thermistor - Wang Beibei; Zhang Liang; Wu Dan; Dong Liang; Zhang Jialin (Dianzi Jishu Yingyong, 2022)
For semiconductor devices, such as IGBT，the high junction temperature will seriously affect the operation characteristics, and such affect the reliability of power electronic devices constructed by them. The real-time on-line temperature monitoring technology based on NTC thermistor is proposed in this paper. By using the negative temperature coefficient(NTC) thermistor integrated inside IGBT module, temperature signals are converted to frequency signals and transferred to the logic processing chip(CPLD) via fiber isolation. The temperature is displayed in real time on computer after logic processing. It has the advantages of high reliability and accurate display. Finally, an engineering prototype of real-time on-line temperature monitoring technology is built to verify the effectiveness of this technology by testing the frequency values at different temperatures under the experiment of the power electronic device.